A 2006-os "kétszeres minimálbér szabály" hatása a szürkegazdaságra - Balázs Reizer (Hungarian Academy of Sciences, Institute of Economics, 2011)
– Since 2006, the law has changed in a way that the expected wage of the employers has to be at least the double of the minimum wage. The employers who pay less than this amount to their employees are more likely to be audited by the tax authority. According to my hypothesis this change has decreased significantly the amount of envelop wages. My aim is to examine empirically the difference between conformation of the legal and informal wages and the behaviour of tax evading companies after the introduction of this new tax law.
Keywords: C51; H26; H32; J31; 330; tax evasion; wage distribution; Steuervermeidung; Lohnstruktur; Ungarn